2017
DOI: 10.1111/phn.12377
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the intervention effect moderators of a cardiovascular health promotion study among rural African‐Americans

Abstract: Knowledge about the moderators that influenced intervention outcomes can assist public health nurses in tailoring health promotion programs for underserved populations that can be implemented in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…MIM DASH did not improve diet, mindfulness affect, or perceived stress. Because diagnosis of hypertension was an inclusion criteria, the participants' knowledge of their heart disease may have exerted a moderating effect on their self‐efficacy to make dietary changes, as is reported in a study of African Americans who participated in a cardiovascular health promotion study 21 . Participants in our study reported low stress and above average mindfulness affect at baseline.…”
Section: Discussionmentioning
confidence: 73%
“…MIM DASH did not improve diet, mindfulness affect, or perceived stress. Because diagnosis of hypertension was an inclusion criteria, the participants' knowledge of their heart disease may have exerted a moderating effect on their self‐efficacy to make dietary changes, as is reported in a study of African Americans who participated in a cardiovascular health promotion study 21 . Participants in our study reported low stress and above average mindfulness affect at baseline.…”
Section: Discussionmentioning
confidence: 73%
“…Digital tools for health management included web-based programmes, [13][14][15][16][17][18][19][20][21][22][23][24][25] mobile phone apps or text messages 20 25-34 and wearables. [35][36][37][38] Community or face-to-face health programmes have been developed for or implemented in churches, 39 rural communities, 40 41 youth healthcare centres, 42 adult day-care centres, 43 paediatric practices, 44 assisted living facilities, 45 hospitals, [46][47][48] mobile health counselling units, 49 schools 50 and workplaces. [51][52][53] We used the model of Gambhir et al 1 to determine the stage in the precision health ecosystem that our reviewed articles focus on.…”
Section: Context and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Designing CBCT programmes with input and developmental insights from cultural groups that they intend to serve allows the programmes to target relevant barriers and challenges, and resources to be applied where most needed 15 16. CBCT programmes have shown promising impacts on chronic disease awareness, condition management, medication adherence, programme satisfaction, condition-specific knowledge, psychosocial factors, and health intervention strategies among black communities 22 29–33. However, the design, structure and operational definition of CBCT programmes varies considerably from programme to programme, making them difficult to compare.…”
Section: Introductionmentioning
confidence: 99%